(untitled) (Ames, Iowa, 2004)
A common goal of human and veterinary medicine is to prevent and cure disease. To reach this goal, there must be a greater investment in the pathophysiology of diseases. Simply put, reductionist methodology fails to answer all of the questions. Pathophysiology represents a new approach to understanding the nature of disease processes, an approach already being embraced in human medicine. By integrating the basic sciences with pathology and the clinical sciences, Veterinary Pathophysiology bridges a significant and widening gulf in the veterinary professional curriculum.
Thâm cứu sinh lý bệnh thú y,Sinh lý bệnh học thú y
Keywords: Veterinary pathophysiology,Animal diseases,Veterinary medicine,Thú y,Bệnh động vật; Physiopathology,Methods